2019
DOI: 10.1177/0091415019857061
|View full text |Cite
|
Sign up to set email alerts
|

Aging With a Physical Disability, Duration of Disability, and Life Satisfaction: A 5-Year Longitudinal Study Among People Aged 40 to 79 Years

Abstract: Studies show that having physical disabilities is associated with lower life satisfaction (LS). People with disabilities have reduced opportunities and welfare compared with people without disabilities. During aging, disabilities may have different impact on LS. A question is whether disability duration plays a unique role by affecting LS or whether an association is caused by other factors. This study analyzed Norwegian panel data ( N = 2,555) including people aged 40 to 79 years at baseline to examine how di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…The results of this study also confirmed that, regardless of disability type, ICT utilization tends to increase the life satisfaction of people with disabilities ( p < .01). In addition, we found that income was associated with the life satisfaction of people with physical disabilities (b = 0.152, p < .01) and brain lesion disabilities (b = 0.345, p < .01), which is consistent with the findings of previous studies (Kim & Han, 2022; Lin & Cheng, 2019; Nicolaisen, Strand, & Thorsen, 2020). However, income was not found to be associated with the life satisfaction of people with visual disabilities and hearing/language disabilities ( p > .05).…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study also confirmed that, regardless of disability type, ICT utilization tends to increase the life satisfaction of people with disabilities ( p < .01). In addition, we found that income was associated with the life satisfaction of people with physical disabilities (b = 0.152, p < .01) and brain lesion disabilities (b = 0.345, p < .01), which is consistent with the findings of previous studies (Kim & Han, 2022; Lin & Cheng, 2019; Nicolaisen, Strand, & Thorsen, 2020). However, income was not found to be associated with the life satisfaction of people with visual disabilities and hearing/language disabilities ( p > .05).…”
Section: Discussionsupporting
confidence: 91%
“… 53 People with physical disabilities should not be forgotten, especially since they already face substantial barriers in their everyday life 10 and have higher risks of mental health issues. 11 , 13 …”
Section: Discussionmentioning
confidence: 99%
“…Individuals living with disabilities, who represent 15% of the global population, 8 commonly encounter challenges while carrying out their daily life activities, without the COVID-19 context, such as barriers to community mobility, 9 difficulties accessing public transportation, 10 reduced access to healthcare services 11 and barriers to communication. 12 Compared to the general population, individuals with disabilities have a higher risk of depression, 11 lower life satisfaction 13 and increased loneliness. 14 Considering the COVID-19 pandemic, the World Health Organization (WHO) stated that additional considerations from governments, healthcare systems, disability service providers, institutional settings, communities and actors are needed for people with disabilities.…”
Section: Introductionmentioning
confidence: 99%
“…People with disabilities have a higher risk of mental health disorders, such as depressive states (Gudlavalleti et al, 2014), reduced life satisfaction (Nicolaisen, 2020) and increased loneliness (Brunes et al, 2019), compared to the general population.…”
Section: Introductionmentioning
confidence: 99%